Two-dimensional barcodes for hardcopy document integrity verification - Teoh, Chin Yew (2008)
Although we live in an electronic age, it cannot be denied that hardcopy documents are still needed in our life, such as land titles, application forms and contracts. However, document forgery is still happening. Forgery makes a document lose its integrity. Integrity means the assurance that the information is authentic and complete. This study proposes a simple, fast and efficient system that provides integrity protection to hardcopy documents. The Integrity Verification System uses two-dimensional barcodes to store integrity information of a document that improves integrity protection of the document. Two-dimensional barcodes have high data capacity and error correction capability. The integrity information stored in the barcode consists of the text content of the document, a timestamp and a tracking number. The timestamp is used to prove that a page is created at a certain period, whereas tracking number is used as an identification number of a document that is created by a user. However, before all these values are encoded into the barcode, they are hashed to enhance the security of the document. In addition, data compression is used in order to efficiently use the storage space of the barcode. The recipient of the document is able to verify the integrity of the document by first scanning the document. The scanned image is then converted to text using an optical character recognition (OCR) module. The text content is then compared with the integrity information encoded in the barcode. If there is any disparity, it means that the document has been tempered. Besides that, data compression techniques and two-dimensional barcodes are also analyzed. The system design is also explained to facilitate the understanding of the system operation. All the techniques in the system are organized into functional modules that build up as the system architecture. This modular structure is useful when there is any upgrading in the future. The particular module can be replaced to improve the system. The Integrity Verification System is an Add-In for Microsoft Office Word 2007 developed using Microsoft Visual Studio 2008 Professional Edition and Microsoft .NET Framework Version 3.5. The system is tested on a permanent test bed to ensure consistent results. The verification testing tests whether the system is capable of verifying a document’s integrity, whereas the modification detection tests whether the system is capable of detecting forgery. The test results are then analyzed and discussed to clearly outline the system’s capability in providing integrity verification services. Results has shown that grayscale images cause less OCR recognition error compared to black/white images and the barcode is high resistant to damage. This study has shown that the integrity verification of a hardcopy document can be performed with the use of two-dimensional barcode. Further studies on better data compression techniques, error correction capabilities of the barcode and other barcode standards can be conducted. The system can also be enhanced with password protection through software or administrator control.